Trace metal concentrations in cupressaceae leaves as biomonitors of environmental pollution - Kaya, G.; Yaman, M. (Dustri-Verlag Dr Karl Feistle, 2008)
The concentrations of lead, cadmium and copper in leaves of cupressaceae species including cupressus sempervirens, cupressus arizonica, and biota thuja were determined by flame atomic absorption spectrophotometry. Plant samples were collected from industrial areas such as the lead battery-production plant and cement factory in Gaziantep-Turkey. Lead concentrations in the leaves of cupressus sempervirens, cupressus Arizona and bioda thuja, grown around the battery production plant were found to be 5,768, 5,340 and 2,200 mgkg(-1), respectively, which are 2,000-times higher than those grown in uncontaminated regions. Cd levels up to 180 and 270 ngg(-1) were found in cupressus arizona and bioda thuja collected around the battery plant and textile industry, respectively. The concentrations described above for Pb, Cd were found to be 10-fold higher than in those other plants collected from the same points. Thus, it was concluded that the plants mentioned above can be used as biomonitors of atmospheric pollution for Pb and Cd. The highest and lowest Cu concentrations were found to be 7.2 and 1.6 mg kg(-1) in the leaves of studied samples, respectively. Lead concentrations in soil samples collected from 300 m distance of battery were found to be higher than the limit levels for agricultural purposes. The observed Cd and Cu concentrations in the studied soil and plant samples were found to be lower than the allowable limit values.
Keywords: biomonitoring; environmental pollution; trace metals; atomic absorption; cupressaceae